Work-family conflict among athletic trainers in the secondary school setting - Pitney, W. A.; Mazerolle, S. M.; Pagnotta, K. D. (Journal of Athletic Training, 2011)
Context: Work-family conflict (WFC) negatively affects a professional's ability to function at work or home.